Aerospace and military [technology 1999 analysis and forecast]. - Braham, R. (IEEE spectrum)
The Pentagon is making good on its new slogans of situational awareness and the age of the digital battlefield. These phrases signify, in essence, a revolutionary change in the time-honored concept of thousands of soldiers toiling as one, both to fight physically and to render information upwards. Many of the same tasks will be done by an astounding diversity of new ?assets?-humans and machines. If the Pentagon devotes equal or more attention to technologies that fuse, filter, and coherently present the overflow of received data, the tactical and strategic opportunities offered by the following systems can only increase. In a sense, new Pentagon designs systematically blur the distinction between the destructive power of weapons and active intelligence agents that facilitate that power. Thus, autonomous weapons of the new type may gather signal intelligence and distribute it to assets it chooses, like a human intelligence agent of old, and phalanxes of unmanned platforms move through unknown environments either as scouts or as fighters, avoiding obstacles and releasing weapons as they choose. Some unmanned air reconnaissance platforms mentioned can traverse continents, and may bulk up to tele-operated attack jets or shrink to butterfly-sized aircraft humming along by themselves. On the field, mines are mutating into wide-area networks of robotic munitions launchers. Thinking even smaller, engineers have come up with networked tell-tale radio-frequency tags and data communications for rifles